PERKEMBANGAN SOSIAL EMOSIONAL ANAK PRA SEKOLAH DENGAN INSTRUMEN KUESIONER MASALAH MENTAL EMOSIONAL - Emsya Salsabela; Siti Khumaeroh; Rr Deni Widjayatri (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
The period of social emotional development of pre-school children needs to be monitored as early as possible with the emotional mental problem questionnaire (KMME) instrument tool useful for early detection in emotional deviations that can be carried out on children aged 36-72 months, namely the pre-school period. The purpose of this study to provide knowledge about the social-emotional development aged 36-72 months of pre-school children. This research activity was carried out at KB Ar-Raudho Serang using descriptive qualitative methods with interview techniques using the KMME instrument. Doing this KMME is useful for parents to know the social emotional development of children by knowing if the child has or does not have emotional problems. The results of the survey, was found from the number of informants 15 children in KB Ar-Raudho Serang there were 6 children who had good emotional abilities, 2 children had an answer of 1